Transition pathway for proximity and social economy (Publications Office of the European Union, 2022)
On 10 March 2020, the Commission adopted a new EU industrial strategy to help the European industry lead the way on green and digital transformation and to boost the EU's global competitiveness and open strategic autonomy. In light of the experience of the COVID-19 pandemic, the Commission updated its EU industrial strategy in May 2021, confirming the need to accelerate the green and digital transitions and increase the resilience of key industrial ecosystems by launching transition pathways. The first Annual Single Market report outlined transition challenges and opportunities for 14 industrial ecosystems, including the 'proximity and social economy' ecosystem. While still addressing the aftershock of the COVID-19 pandemic and facing the new economic shocks of the unjustified Russian invasion of Ukraine, the priorities of the EU industrial strategy (resilience, the green and digital twin transition and open strategic autonomy) regain their relevance within the current geopolitical and economic context. Achieving the European Green Deal objectives of transition to climate neutrality by 2050 and meeting the Digital Compass targets for 2030 will require profound changes of economic and business models, backed by substantial and targeted investments to sustain recovery and competitiveness. This is particularly the case for the 'proximity and social economy' industrial ecosystem, which encompasses entrepreneurship models of diverse scale and capacity (hereafter referred as 'the ecosystem'). Parts of the social economy contribute to the green and digital transitions at large by supplying sustainable goods and services and bridging the digital divide. Their participatory business models, that take into account the needs of citizens, employees and other stakeholders, help to ensure that the transitions are fair and inclusive. At the same time, reinforcing sustainable and digital practices within the whole ecosystem will build long-term resilience and allow its diverse actors to be active levers of the twin transition. Against this background, a pathway for the green and digital transition of the 'proximity and social economy' ecosystem is presented. The action areas outlined in the transition pathway resulted from a co-creation process with stakeholders launched in December 2021, on the occasion of the adoption of the European Action Plan for the social economy, which sets out the EU vision on social economy for 2030 and whose implementation the transition pathway underpins.
10.2873/44306
Keywords: Graue Literatur; social economy; EU industrial policy; digital transformation; green economy; competitiveness; single market; carbon neutrality; investment; sustainable development; goods and services; business model; community resilience; action programme; EU research policy; innovation